Development of Life Skill-Based Learning Instruments: Biotechnology Material in Junior High School - Sekar Jatiningrum Parnonansia; Dewi Mustikaningtyas (Biosaintifika: Journal of Biology & Biology Education, 2015)
The result of preliminary observations in Empu Tantular Semarang junior high school showed that the learning instruments was still focused on the achievement of cognitive competence. The present study aimed to develop a life skill-based learning instruments of biotechnologi material. Learning instruments including syllabi, lesson plans, worksheets, scale attitudes sheets, and vocational skills assessment sheet, as well as to test its feasibility and effectiveness. This study was Research and Development, whereas the trial product design was a One Shot Case Study pattern. Trials of limited scale and large scale were done in the student of class IX at odd semester of year 2014/2015. The results of the three expert assessment of learning instruments showed very feasible criteria to be used. Inter-rater correlation analyzes were performed using the SPSS16 program which obtained a yield of 0.99. It indicated that the inter-rater reliability was exceptionally high. Classical completeness to the cognitive learning, affective and vocational skills of students of class IX A were 92.1%; 97.4%; 92.1%, respectively. Meanwhile, the results of class IX D were 74.4%; 94.9%; 100%, respectively. The percentage of student who reach the level of adherence to the learning ≥61% were 100% in class IX A and 87.2% in class IX D. Therefore, the developed learning instrument was fit to be used and also effectively applied in the Empu Tantular Semarang junior high school. Beside of improving student cognitive competence in Empu Tantular Semarang junior high school,  development of life skill-based learning instruments can also provide knowledge and skills that can be used so that students can make a positive contribution in later life as a member of the family and society. Hasil Observasi awal di SMP Empu Tantular Semarang, menunjukkan perangkat pembelajaran yang diterapkan masih terfokus pada pencapaian kompetensi kognitif. Penelitian ini bertujuan untuk mengembangkan perangkat pembelajaran IPA berbasis kecakapan hidup materi bioteknologi yang meliputi silabus, RPP, LKS, dan instrumen penilaian serta menguji kelayakan dan efektivitasnya. Metode penelitian yang digunakan adalah Research and Development (RD). Desain uji coba produk menggunakan pola One Shot Case Study. Uji coba skala terbatas dan skala luas dilakukan pada peserta didik kelas IX semester gasal tahun ajaran 2014/2015. Hasil penilaian dari ketiga pakar terhadap silabus, RPP, LKS, lembar skala sikap, dan lembar penilaian kecakapan vokasional mencapai kriteria Very Feasible digunakan. Analisis korelasi inter rater yang dilakukan menggunakan program SPSS16 memperoleh hasil sebesar 0,99. Hal ini menunjukkan bahwa reliabilitas inter rater/antar penilai tergolong sangat tinggi. Ketuntasan klasikal untuk hasil belajar kognitif, afektif dan kecakapan vokasional dari kelas IX A berturut turut 92,1%; 97,4%; 92,1% dan kelas IX D berturut turut 74,4%; 94,9%; 100%. Persentase jumlah anak yang mencapai tingkat keterlaksanaan pembelajaran ≥ 61% dari kelas IX A sebesar 100% dan kelas IX D sebesar 87,2%.Perangkat pembelajaran yang dikembangkan Very Feasible digunakan dan efektif diterapkan di SMP Empu Tantular Semarang.